Plating method and wiring board obtained by using said method

JP7644928B2Active Publication Date: 2025-03-13KANTO GAKUIN SCHOOL CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021038913
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-11
Publication Date
2025-03-13
Estimated Expiration
2041-03-11

AI Technical Summary

Benefits of technology

【0017】 本発明によれば、樹脂材と金属からなる配線との密着性を高めると共に処理コストを抑えながらも、高周波回路用として好適な配線を安定的に形成することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644928000002
    Figure 0007644928000002
  • Figure 0007644928000001
    Figure 0007644928000001
Patent Text Reader

Abstract

To provide a plating method capable of stably enhancing adhesion to a wiring consisting of a resin material and metal and forming the wiring suitable for high frequency circuits even while suppressing treatment cost, and a wiring board obtained using the same.SOLUTION: A plating method of forming a conductor layer only in a place irradiated with ultraviolet on the surface of a resin material comprises: an ultraviolet irradiation step of irradiating a surface to be plated having 500 nm or less of an arithmetic average height Sa of the resin material obtained by non-contact type measurement using a laser beam microscope with the ultraviolet at a level without causing shape deformation; a degreasing step of contacting a 25-60°C degreasing agent to the surface to be plated of the resin material for 5-10 minutes to perform degreasing; and a step of performing plating to form the conductor layer.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a plating method and a wiring board obtained by using the method. [Background technology]

[0002] In recent years, electronic devices have become lighter, thinner, shorter, smaller, more powerful, and more diverse in shape. In addition, in recent years, various sensors are used in the age of IoT (Internet of Things), and it may be difficult to adapt to flat substrates on which wiring circuits are formed. For this reason, molded interconnected devices (MIDs), which can form wiring circuits on the surface of small, complex-shaped substrates, are expected to become a trend in various industrial fields such as communications, medicine, and automobiles. In light of this background, future electronic devices will require further miniaturization of the wiring on the wiring boards that constitute them, as well as further improvement in the adhesion between the wiring and the wiring substrate.

[0003] In order to reduce the transmission loss of signals, a resin material with a low dielectric constant is mainly used as the raw material for the wiring substrate. Therefore, electroless plating is mainly used when forming a wiring (conductor layer) made of metal on the surface of a resin material. However, when a conductor layer is formed on the surface of a resin material by electroless plating, the adhesion between the resin material and the conductor layer is likely to be insufficient. In this case, in the conventional method of roughening the surface of the resin material by etching with an etching solution (conventional potassium permanganate or sodium manganate, or recent sulfuric acid-hydrogen peroxide-based chemical solution, etc.) and obtaining adhesion between the resin material and the conductor layer by utilizing the anchor effect, the surface smoothness of the resin material is reduced, and a fine wiring pattern cannot be formed with high accuracy. In addition, the conductor layer obtained by the conventional method utilizing the anchor effect has a large surface roughness, and when a high-frequency signal of 1 GHz or more is transmitted, the influence of the skin effect appears, which may lead to a deterioration in transmission characteristics. When a conductor layer with a large surface roughness is used in an electronic device, a problem occurs in that the electrical characteristics cannot be improved.

[0004] In response to the above-mentioned problems, the laser direct structuring (LDS) method has been put to practical use. In the LDS method, a resin material for forming wiring circuits is used that contains an LDS additive containing an organometallic compound (metal complex) that is activated by laser irradiation. Currently, an infrared laser is irradiated to the resin material at a location where wiring is to be formed, so that the organometallic compound present in the laser irradiated area is exposed to the surface and activated as a catalyst. As a result, an electroless plating film can be selectively formed in the area where wiring is to be formed. Furthermore, in the LDS method, a laser treatment is performed on the resin material, so that a roughening treatment can be performed on the surface of the area where wiring is to be formed. Therefore, the plating film that becomes the wiring can be firmly fixed to the surface of the resin material due to the anchor effect. Note that the technology related to the LDS method is disclosed in, for example, Patent Document 1 and Patent Document 2. Since the LDS method employs laser treatment, it is possible to form fine and complex wiring with high precision by scanning the laser even in a three-dimensional wiring board. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Special Publication No. 2004-534408 [Patent Document 2] Special Publication No. 2010-536947 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the LDS method, the LDS additives mixed into the resin material must be exposed, which requires extra laser irradiation. Therefore, when the LDS method is used, the roughness of the plated surface increases, and the final wiring board may not be suitable for high-frequency circuits. In addition, since the LDS method requires the mixing of LDS additives into the resin material, depending on the type of LDS additive, the properties of the resin material (mechanical strength, etc.) may be adversely affected. Furthermore, since the LDS method uses special LDS additives, the management of the plating process may become complicated.

[0007] In view of the above, an object of the present invention is to provide a plating method that can stably form a conductor layer suitable for use in high-frequency circuits while increasing the adhesion between a resin material and a conductor layer and reducing processing costs, and a wiring board obtained using the same. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have achieved the above object by employing the following plating method and a wiring board obtained using said method.

[0009] The plating method of the present invention is a plating method for forming a conductor layer only at the locations on the surface of a resin material that have been irradiated with ultraviolet light, and is characterized in that it includes an ultraviolet light irradiation step of irradiating a surface of the resin material to be plated, the surface having an arithmetic mean height Sa of 500 nm or less as measured by non-contact measurement using a laser microscope, with ultraviolet light to an extent that does not cause deformation of the surface, and a degreasing step of degreasing the surface of the resin material to be plated by contacting the surface with a degreaser at 25 to 60°C for 5 to 10 minutes after the ultraviolet light irradiation step, and then performing a plating process to form the conductor layer.

[0010] In the plating method according to the present invention, it is preferable that the difference in the arithmetic mean height Sa of the surface to be plated immediately before and after the ultraviolet ray irradiation step is set to 10 nm to 1000 nm.

[0011] In the plating method according to the present invention, it is preferable that the difference in the arithmetic mean height Sa of the surface to be plated immediately before and after the degreasing step is set to 3 nm to 10 nm.

[0012] In the plating method of the present invention, it is preferable that the plating process includes a sensitizing process in which the surface to be plated is contacted with a solution containing stannous chloride as a main component for 30 seconds to 3 minutes to adsorb tin ions, an activating process after the sensitizing process in which the surface to be plated is contacted with a solution containing palladium chloride as a main component for 30 seconds to 3 minutes to precipitate palladium, and a conductor layer formation process in which the conductor layer is formed on the surface to be plated by plating after the activating process.

[0013] In the plating method of the present invention, the conductor layer forming step preferably comprises forming a nickel-phosphorus layer having a thickness of 0.1 to 5 μm on the surface to be plated, and then forming a copper layer having a thickness of 10 to 35 μm on the surface of the nickel-phosphorus layer.

[0014] In the plating method according to the present invention, the plating bath used in the conductor layer forming step preferably has a bath temperature of 50°C to 80°C.

[0015] In the plating method according to the present invention, the resin material is preferably an epoxy resin material, a liquid crystal polymer material, a polyphenylene sulfide resin material, or an ABS resin material.

[0016] The wiring board according to the present invention is characterized in that it is obtained by using the plating method described above. Effect of the Invention

[0017] According to the present invention, it is possible to stably form wiring suitable for use in high frequency circuits while increasing the adhesion between a resin material and metal wiring and reducing processing costs. [Brief description of the drawings]

[0018] [Figure 1] FIG. 2 is a flow diagram showing a configuration of a wiring forming method according to the present embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Hereinafter, embodiments of the plating method according to the present invention and the wiring board obtained by using the method will be described. However, the aspects of the present invention are not limited to the embodiments described below.

[0020] A. Plating method according to the present invention The plating method according to the present invention is a plating method for forming a conductor layer only at the ultraviolet irradiated portion of the resin material surface. The plating method includes an ultraviolet irradiation step of irradiating ultraviolet rays to a degree that does not cause deformation on the surface of the resin material to be plated, the surface having an arithmetic mean height Sa (a surface roughness parameter defined in ISO25178, the same applies below) of 500 nm or less as measured by a non-contact method using a laser microscope, and a degreasing step of contacting the surface of the resin material to be plated with a degreaser at 25 to 60°C for 5 to 10 minutes to degrease the surface. After that, plating is performed to form the conductor layer. The ultraviolet irradiation step and the degreasing step as pre-plating treatments of the present invention are described below.

[0021] A-1. Pre-plating treatment The ultraviolet irradiation step and the degreasing step will be described below separately.

[0022] <About the ultraviolet irradiation process> The plating method according to the present invention has a step of irradiating the surface to be plated with ultraviolet light to an extent that does not cause deformation of the surface, instead of an etching step for obtaining an anchor effect or a surfactant adsorption step for promoting the application of a catalyst. In the ultraviolet light irradiation step, the surface to be plated of the resin material forming the conductor layer is irradiated with ultraviolet light to modify the surface to be plated to be hydrophilic. By improving the hydrophilicity of the surface to be plated, it becomes easier for a metal that can function as a catalyst to be adsorbed on the surface to be plated, and it becomes possible to chemically improve the adhesion at the interface between the resin material and the conductor layer.

[0023] Here, the above-mentioned modification for changing the surface of the resin material to hydrophilicity will be described. This modification improves the structural characteristics and functionality of the plated surface of the resin material by irradiating it with ultraviolet light. Specifically, the chemical bonds of the polymers on the surface of the resin material are broken by irradiating the resin material with ultraviolet light of an appropriate wavelength, and functional groups (hydrophilic groups such as hydroxyl groups (-OH) and carboxyl groups (-COOH)) are generated on the surface of the resin material due to oxidation. This modification makes it possible to selectively adsorb catalyst ions to the resin material when electroless plating is performed.

[0024] In the plating method according to the present invention, the wavelength range of the ultraviolet light irradiated onto the resin material may be appropriately selected within the range of 150 to 400 nm, depending on the type of the resin material. By irradiating the surface of the resin material to be plated with ultraviolet light having a wavelength appropriate for the type of the resin material, the surface to be plated is oxidized and hydrophilic groups are imparted. In general, the more hydrophilic groups there are, the greater the hydrophilicity.

[0025] In the plating method according to the present invention, the above-mentioned ultraviolet ray generating source is not particularly limited, and can be appropriately selected from UV lamps, gas lasers, solid-state lasers, etc. Here, examples of the gas laser include excimer lasers such as KrF lasers and ArF lasers. Examples of the solid-state laser include YAG lasers. For reference, the excimer laser has a short wavelength and can perform fine processing. Furthermore, since it has excellent scannability, it is easier to form so-called three-dimensional wiring on the surface of the resin material, even if the resin material has a complex three-dimensional shape, than other ultraviolet ray generating sources.

[0026] In the plating method according to the present invention, the above-mentioned resin material can be any resin material whose surface to be plated can be modified by irradiation with ultraviolet light. For example, the resin material can be a thermoplastic resin such as LCP (liquid crystal polymer), PPS (polyphenylene sulfite resin), POM (polyacetal), PC (polycarbonate), PMMA (polymethyl methacrylate), PET (polyethylene terephthalate), PE (polyethylene), PP (polypropylene), PS (polystyrene), PVC (polyvinyl chloride), ABS (acrylonitrile-butadiene-styrene polymer), or a thermosetting resin such as PE (phenol resin) or EP (epoxy resin). Among the resin materials listed here, it is particularly preferable to use an epoxy resin material, a liquid crystal polymer material, a polyphenylene sulfide resin material, or an ABS resin material, in consideration of their usefulness as wiring board materials and their suitability for high-frequency wiring boards.

[0027] In the plating method according to the present invention, the resin material used has an arithmetic mean height Sa of the plated surface of 500 nm or less. By irradiating the plated surface that satisfies this condition with ultraviolet light to an extent that does not cause deformation of the shape, the plated surface can be modified to be hydrophilic while maintaining a fine structure of the nanometer order. If the surface smoothness of the plated surface is at this level, when a conductor layer is formed on the plated surface, the transmission loss in the high frequency region of the conductor layer is reduced. In addition, in the conductor layer, when stabilizing the suppression of transmission loss in the high frequency region and improving the transmission loss in the ultra-high frequency region of 10 GHz or more are intended, the arithmetic mean height Sa of the plated surface is more preferably 300 nm or less, and even more preferably 60 nm or less. If the high frequency circuit has an arithmetic mean height Sa of the plated surface of 60 nm or less, it can be suitably used in electronic devices using high frequencies of the next generation communication standards "5G" and "6G".

[0028] In the plating method according to the present invention, the condition of ultraviolet irradiation on the surface of the resin material to be plated is set to a level that does not cause deformation of the surface. However, in consideration of forming a conductor layer suitable for a circuit corresponding to high-speed transmission and improving the adhesion between the resin material and the conductor layer to a level required for a high-frequency circuit board, it is preferable that the difference in the arithmetic mean height Sa of the surface to be plated immediately before and immediately after the ultraviolet irradiation process is 10 nm to 1000 nm. Here, if the difference in the arithmetic mean height Sa of the surface to be plated immediately before and immediately after the ultraviolet irradiation process is less than 10 nm, the surface to be plated cannot be sufficiently modified to be hydrophilic, and the adhesion between the resin material and the conductor layer cannot be stably improved. On the other hand, if the difference in the arithmetic mean height Sa of the surface to be plated exceeds 1000 nm, a large transmission loss occurs in the signal current when transmitting a high-frequency signal in the conductor layer formed on the surface to be plated, which is not preferable. The upper limit of the difference in the arithmetic mean height Sa of the plated surface is preferably 200 nm, and more preferably 60 nm, in order to stably and sufficiently obtain the above-mentioned effect of "forming a conductor layer suitable for circuits compatible with high-speed electrical transmission."

[0029] <About the degreasing process> In the plating method according to the present invention, after the above-mentioned ultraviolet irradiation step, the surface of the resin material to be plated is subjected to a degreasing step under the following conditions, so that the adhesion at the interface between the resin material and the conductor layer can be physically improved without changing the surface roughness of the surface to be plated as much as possible. That is, when the surface of the resin material to be plated is irradiated with ultraviolet light in the above-mentioned ultraviolet irradiation step, a photodecomposition process is performed on the surface to be plated, which cuts the molecular chain of the intermolecular bond. Then, by performing the degreasing step of the present invention, the processing residue generated during the photodecomposition process is removed, and a surface having fine irregularities of the nanometer order having an anchor effect is formed on the surface to be plated. As a result, it is possible to minimize the increase in the surface roughness of the surface to be plated, while ensuring the necessary and sufficient adhesion between the resin material and the conductor layer.

[0030] In the degreasing step of the present invention, a degreaser at 25 to 60°C is brought into contact with the surface of the resin material to be plated for 5 to 10 minutes to perform degreasing. The degreaser used in the degreasing step of the present invention is not particularly limited, but known degreasers such as an alkaline degreaser containing a sodium hydroxide solution or an acidic degreaser can be appropriately adopted. Here, if the temperature of the degreaser is less than 25°C or the time for which the degreaser is brought into contact with the surface of the resin material is less than 5 minutes, the processing residue generated in the above-mentioned ultraviolet irradiation step cannot be sufficiently removed, and the adhesion between the resin material and the conductor layer cannot be stably improved. In addition, since it is difficult to completely remove the oil and fat, dirt, etc. attached to the resin material, the adsorption force of the metal catalyst cannot be improved in the subsequent step, and the plating cannot be sufficiently precipitated on the surface to be plated. On the other hand, if the temperature of the degreaser exceeds 60°C or the time for which the degreaser is brought into contact with the surface of the resin material exceeds 10 minutes, not only the surface to be plated of the resin material but the entire surface becomes hydrophilic, which may lead to a decrease in selective plating properties. In the degreasing step of the present invention, the method for bringing the degreasing agent into contact with the surface of the resin material is not particularly limited, and a dipping method or a spraying method can be adopted.

[0031] In addition, in the plating method according to the present invention, the difference in the arithmetic mean height Sa of the plated surface of the resin material immediately before and after the degreasing step is preferably 3 nm to 10 nm. By contacting the plated surface of the resin material with the degreasing agent so as to satisfy this condition, it is possible to secure sufficient adhesion between the resin material and the conductor layer, and to more stably form a conductor layer suitable for circuits corresponding to high-speed transmission. Here, if the difference in the arithmetic mean height Sa of the plated surface immediately before and after the degreasing step is less than 3 nm, the adhesion strength between the resin material and the conductor layer cannot be sufficiently improved. On the other hand, if the difference in the arithmetic mean height Sa of the plated surface exceeds 10 nm, the conductor layer formed on the plated surface is significantly affected by the skin effect on high-frequency signals, which may cause a delay in transmission signals.

[0032] From the above, the plating method according to the present invention, by adopting the above-mentioned pre-plating treatment, can improve the selective plating required for forming highly precisely patterned circuit wiring while maintaining the desired adhesive strength between the resin material and the conductor layer, without using a special LDS additive as in the LDS method. Furthermore, by adopting the above-mentioned pre-plating treatment, the processing steps can be simplified.

[0033] Next, the plating method of the present invention preferably includes, as plating processes, "a sensitizing treatment step in which a solution containing stannous chloride as a main component is brought into contact with the surface of a resin material for 30 seconds to 3 minutes to adsorb tin ions", "an activating treatment step in which, after the sensitizing treatment step, a solution containing palladium chloride as a main component is brought into contact with the surface of the resin material to be plated for 30 seconds to 3 minutes to precipitate palladium", and "a conductor layer formation step in which, after the activating treatment step, a conductor layer is formed by plating on the surface of the resin material to be plated".

[0034] In the plating method according to the present invention, the above-mentioned sensitizing process and activating process are performed in this order, so that the amount of catalyst adsorbed on the ultraviolet ray irradiated surface is increased, and selective plating deposition is possible in the conductor layer formation process due to the difference in activity with respect to the ultraviolet ray non-irradiated surface. Note that in the plating method according to the present invention, the sensitizing process and the activating process can be performed repeatedly multiple times. The sensitizing process, activating process, and conductor layer formation process, which are the plating processes of the present invention, are described below.

[0035] A-2. Plating process The following description will be made separately for a sensitizing process, an activating process, and a conductor layer forming process.

[0036] <About the sensitizing process> In the sensitizing process of the present invention, a solution containing stannous chloride as a main component is brought into contact with the surface of the resin material for 30 seconds to 3 minutes to generate tin ions (Sn 2+ ) is adsorbed. By adsorbing tin ions having a strong reducing power to the surface to be plated of the resin material under these conditions after the above-mentioned degreasing process, active palladium catalyst nuclei can be adsorbed to the surface to be plated in the subsequent activating process, and a conductor layer can be uniformly formed on the surface to be plated. In order to stably obtain such an effect, the tin concentration in the solution is preferably 1 to 100 mmol / L. Here, when the time for contacting the surface of the resin material with the solution containing stannous chloride as a main component is less than 30 seconds, the tin ions cannot be sufficiently adsorbed on the surface to be plated of the resin material, and therefore the selective plating property cannot be sufficiently improved. On the other hand, when the time for contacting the surface of the resin material with the solution containing stannous chloride as a main component is more than 3 minutes, the effect of uniformly forming a conductor layer on the surface to be plated is saturated, and there is no cost merit.

[0037] <About the activation process> In the activating (catalyzing) treatment process of the present invention, a solution containing palladium chloride as a main component is brought into contact with the surface of the resin material for 30 seconds to 3 minutes to introduce palladium ions (Pd 2+ ) is precipitated as palladium metal (Pd). By precipitating palladium (palladium activation) as a catalyst nucleus on the surface of the resin material to be plated under these conditions after the above-mentioned sensitizing treatment process, the electroless plating reaction can be improved in the subsequent process, and a conductor layer can be uniformly formed on the surface to be plated. Since palladium is soluble in hydrochloric acid, 0.1 to 10 ml / L of concentrated hydrochloric acid is added. In order to stably obtain such effects, the palladium concentration in the solution is preferably 0.1 to 5 mmol / L. Here, if the time for contacting the surface of the resin material with the solution containing palladium chloride as a main component is less than 30 seconds, palladium cannot be sufficiently precipitated on the surface to be plated of the resin material, and therefore the selective plating property cannot be sufficiently improved. On the other hand, if the time for contacting the surface of the resin material with the solution containing palladium chloride as a main component is more than 3 minutes, the effect of uniformly forming a conductor layer on the surface to be plated is saturated, and there is no cost merit.

[0038] In addition, the plating method according to the present invention preferably includes a depalladium step between the above-mentioned activating treatment step and the conductor layer forming step described below, which removes palladium adsorbed on the part of the resin material that is not irradiated with ultraviolet light. By adopting this depalladium step, the selective plating property can be further improved. Here, the method of removing palladium is not particularly limited, and for example, a method of immersing the resin material in an aqueous solution containing trisodium citrate solution or a commercially available palladium remover can be adopted.

[0039] The above-mentioned sensitizing process and activating process are known as a method of adding a catalyst to a non-conductive base material such as a resin material, and are processes that are carried out using a "sensitizer-activator process" that utilizes the reducing power of tin ions. In the present invention, by adopting this sensitizer-activator process as a plating process, it becomes possible to stably form a uniform conductive layer in the subsequent conductive layer formation process.

[0040] In addition, although the sensitizer-activator method has been described above as a palladium activation method, the plating method according to the present invention is not limited to this method. The sensitizer-activator method is a so-called two-liquid type treatment in which separate treatment solutions are used for the sensitizer treatment and the activator treatment, but the plating method according to the present invention can also adopt a so-called one-liquid type treatment in which palladium activation is performed using one treatment solution. In the one-liquid type treatment, for example, a solution containing palladium chloride and tin chloride in an acidic hydrochloric acid aqueous solution, a solution containing palladium chloride and tin chloride in a weakly acidic salt-type aqueous solution, an aqueous solution containing a palladium complex, or the like can be used as a treatment solution. In addition, an acceleration treatment can be performed thereafter to remove excess tin as necessary.

[0041] <Conductor layer formation process> The conductor layer forming process of the present invention is a process for forming a conductor layer on the surface to be plated of a resin material after the above-mentioned activating process. The conductor layer formed in the conductor layer forming process can maintain the surface to be plated in a nanometer-order fine structure while increasing the adhesion of the conductor layer to the surface to be plated by passing through a sensitizer-activator method. Therefore, the conductor layer formed in the conductor layer forming process of the present invention can stably transmit high-frequency signals without delay, and when used in electronic devices, it is possible to further improve the electrical characteristics. In addition, in this conductor layer forming process, either an electrolytic plating process or an electroless plating process may be used as a method for forming the conductor layer. In addition, the conditions of these plating processes are not particularly limited, and known conditions can be appropriately adopted. Therefore, any additive (such as a complexing agent such as citric acid or a stabilizer such as lead or bismuth) can be added to the plating bath used in the plating process.

[0042] The temperature of the plating bath used in the above-mentioned plating treatment is not particularly limited, but is preferably 50°C to 80°C. When the temperature of the plating bath satisfies this condition, when a resin material to which a catalyst has been applied is immersed in the plating bath, a plating is stably deposited on the surface of the resin material. Here, when the temperature of the plating bath is less than 50°C, the plating deposition rate may decrease, which is not preferable. On the other hand, when the temperature of the plating bath exceeds 80°C, defects such as swelling, cracking, and peeling may occur in the formed plating film, which is not preferable.

[0043] In addition, the conductor layer forming step of the present invention preferably includes forming a nickel-phosphorus layer having a thickness of 0.1 to 5 μm on the surface of the resin material to be plated, and then forming a copper layer having a thickness of 10 to 35 μm on the surface of the nickel-phosphorus layer. The nickel-phosphorus layer can be formed to a uniform thickness by plating without being affected by the shape of the surface of the resin material to be plated, and can further strengthen the adhesion to the resin material. Therefore, by having such a layer structure, the conductor layer of the present invention can maintain the bonding strength at the interface between the resin material and the conductor layer while suppressing the transmission loss of high-frequency signals to a small level.

[0044] Here, if the thickness of the nickel-phosphorus layer is less than 0.1 μm, the strength of the conductor layer is reduced, and the coating of the nickel-phosphorus layer is insufficient, making it impossible to obtain a sufficient anchor effect on the resin material. On the other hand, if the thickness of the nickel-phosphorus layer is more than 5 μm, it takes a long time to form the nickel coating, and there is no cost advantage.

[0045] In addition, when the thickness of the copper layer is less than 10 μm, the effect of improving the bonding strength with the nickel-phosphorus layer cannot be sufficiently obtained, whereas when the thickness of the copper layer is more than 35 μm, it takes a long time to form the copper layer, and there is no cost advantage.

[0046] B. Circuit Board According to the Present Invention The wiring board according to the present invention is characterized by being obtained by using the plating method according to the present invention described above. Therefore, the wiring board according to the present invention has excellent adhesion between the wiring (conductor layer) and the wiring substrate even if the wiring is miniaturized. Furthermore, the wiring board according to the present invention has a low surface roughness of the wiring, and signal delay due to the skin effect is suppressed, making it suitable for use in high-frequency circuits.

[0047] The plating method according to the present invention and the wiring board using the same have been described above, but the present invention will be described in more detail below by showing examples of the present invention. Note that the present invention is not limited to these examples. EXAMPLES

[0048] In this Example 1, an LCP substrate with a size of 50 mm x 50 mm x 5 mm thickness and an arithmetic mean height Sa of 500 nm was prepared as a test specimen as a resin material. A rectangular conductor layer with a width of 10 mm and a length of 50 mm was formed on the surface of the resin material by plating. Specifically, as shown in the flowchart of FIG. 1, an ultraviolet irradiation process (step S10), an alkaline degreasing process (step S20), a sensitizing process (step S30), an activating process (step S40), a depalladium process (step S50), an electroless nickel-phosphorus plating process (step S60), and an electroless copper plating process (step S70) were performed in this order to form a conductor layer on the surface of the resin material. Then, the conductor layer (plating film) formed using this plating method was examined for the selectivity of plating, the smoothness of the plating film surface, and the adhesion of the plating film to the resin material.

[0049] In this Example 1, an ultraviolet irradiation process and an alkaline degreasing process were carried out as plating pretreatments. In the ultraviolet irradiation process, ultraviolet rays were irradiated onto the surface to be plated of the resin material by a KrF laser. At this time, the difference in the arithmetic mean height Sa of the surface to be plated immediately before and immediately after the ultraviolet irradiation process was 12 nm. Thereafter, in the alkaline degreasing process, the resin material was immersed in a sodium hydroxide solution (manufactured by Nippon Kangen Co., Ltd., "Product No.: K-350") at 40°C for 5 minutes to perform alkaline degreasing. At this time, the difference in the arithmetic mean height Sa of the surface to be plated immediately before and immediately after the degreasing process was 5 nm.

[0050] Next, the plating process included a sensitizing process, an activating process, a depalladium process, an electroless nickel-phosphorus plating process, and an electroless copper plating process. In the sensitizing process, the resin material to be tested was immersed in a solution containing stannous chloride as the main component (product name: Pink Sumer, manufactured by Nippon Kanigen Co., Ltd.) for 3 minutes. Then, in the activating process, the resin material was immersed in a solution containing palladium chloride as the main component (product name: Red Sumer, manufactured by Nippon Kanigen Co., Ltd.) diluted to one-fourth the normal concentration for 3 minutes to allow the catalyst to be adsorbed on the surface to be plated. Then, in the depalladium process, the resin material was immersed in a trisodium citrate solution (20 g / L) for 5 minutes while stirring (300 rpm). Thereafter, in the electroless nickel-phosphorus plating process, the surface to be plated was plated for 15 minutes using an electroless nickel plating solution ("Shumer SK101" manufactured by Nippon Kangen Co., Ltd.) (temperature: 70°C, pH: 10). Then, in the electroless copper plating process, immediately after the electroless nickel-phosphorus plating process, a plating process was performed for 15 minutes using an electroless copper plating solution ("OPC Copper MIC-BL" manufactured by Okuno Chemical Industries Co., Ltd.) (temperature: 70°C, pH: 10).

[0051] In Example 1, the selective plating property was evaluated for the plating film obtained through each of the above-mentioned steps. Specifically, in the evaluation of selective plating property, whether or not plating was accurately deposited at a predetermined location on the surface to be plated was confirmed by an electron microscope (magnification: 100 times). Here, the evaluation of selective plating property was performed as follows: "Good" indicates that an electroless nickel-phosphorus plating film was completely formed on the ultraviolet ray irradiated portion and no plating deposition was observed on the ultraviolet ray unirradiated portion; "Good" indicates that even a small amount of plating non-deposition was observed on the ultraviolet ray irradiated portion or even a small amount of plating deposition was observed on the ultraviolet ray unirradiated portion; and "Poor" indicates that the plating non-deposition was significant on the ultraviolet ray irradiated portion or the plating deposition was significant on the ultraviolet ray unirradiated portion.

[0052] In Example 1, the smoothness of the plated film surface was evaluated for the plated film obtained through the above-mentioned steps. The smoothness of the plated film surface was evaluated by the arithmetic mean height Sa. At this time, the arithmetic mean height Sa was measured using a laser microscope "VK-X type manufactured by Keyence Corporation". Assuming that the surface roughness of the plated film transmits a high-frequency signal in the 1 GHz band, the arithmetic mean height Sa of less than 600 nm was rated as "◯", the arithmetic mean height Sa of 600 nm or more and less than 1000 nm was rated as "△", and the arithmetic mean height Sa of 1000 nm or more was rated as "×". For reference, the surface roughness of the plated film in Example 1 was about 550 nm in terms of the average arithmetic mean height Sa.

[0053] Furthermore, in Example 1, the adhesion of the plating film obtained through each of the above-mentioned steps was evaluated by a test method called stud pull. Specifically, an aluminum stud pin (diameter 7.1 mm) was bonded to the surface of the plating film formed on the surface of a resin material using an adhesive, and while supporting the resin material, a vertical tensile load (1.0 kg / s) was applied to the stud pin, and the load (kg / cm2) at the breaking point was measured. 2 ) was measured.

[0054] The results of checking the selective plating property, plating smoothness, and plating adhesion under the above-mentioned conditions are shown in Table 1. In addition to Example 1, Table 1 also shows the results of Examples 2 and 3 and Comparative Examples 1 to 3. EXAMPLES

[0055] In Example 2, the selectivity of plating, the smoothness of the plating film surface, and the adhesion of the plating film to the resin material were confirmed in the same manner as in Example 1. In Example 2, the same resin material as in Example 1 was prepared as a test specimen. In Example 2, the steps shown in the flow chart of FIG. 1 were carried out in the same manner as in Example 1, and a conductor layer was formed on the surface of the resin material.

[0056] The conditions in Example 2 that differ from Example 1 are that in the ultraviolet irradiation step, the difference in the arithmetic mean height Sa of the plated surface immediately before and immediately after the ultraviolet irradiation step is 58 nm, in the alkaline degreasing step, the plated surface is immersed in a sodium hydroxide solution at 25°C, and the difference in the arithmetic mean height Sa of the plated surface immediately before and immediately after the degreasing step is 3 nm, and in the sensitizing treatment step and the activating treatment step, the resin material is immersed for 1 minute. Details of each step shown in the flow chart in Figure 1 have already been explained in Example 1, so they will not be repeated here.

[0057] Table 1 shows the results of checking the selective plating property, plating smoothness, and plating adhesion under the above-mentioned conditions. For reference, the surface roughness of the plating film in Example 2 was about 590 nm in terms of the average arithmetic mean height Sa. Here, the same methods as in Example 1 were used to check these properties. Therefore, a description of these methods will be omitted. EXAMPLES

[0058] In Example 3, the selectivity of plating, the smoothness of the plating film surface, and the adhesion of the plating film to the resin material were confirmed in the same manner as in Example 1. In Example 3, the same resin material as in Example 1 was prepared as a test specimen. In Example 3, the steps shown in the flow chart of FIG. 1 were carried out in the same manner as in Example 1, and a conductor layer was formed on the surface of the resin material.

[0059] The conditions in Example 3 that differ from Example 1 are that in the ultraviolet irradiation step, the difference in the arithmetic mean height Sa of the plated surface immediately before and immediately after the ultraviolet irradiation step is 6 nm, in the alkaline degreasing step, the plated surface is immersed in a sodium hydroxide solution at 25° C. and the difference in the arithmetic mean height Sa of the plated surface immediately before and immediately after the degreasing step is 3 nm, in the sensitizing treatment step and the activating treatment step, the resin material is immersed for 30 seconds, and in the electroless nickel-phosphorus plating treatment step and the electroless copper plating treatment step, the temperature of the plating bath is 60° C. Details of each step shown in the flow chart in FIG. 1 have already been explained in Example 1, so they will not be repeated here.

[0060] Table 1 shows the results of checking the selective plating property, plating smoothness, and plating adhesion under the above-mentioned conditions. For reference, the surface roughness of the plating film in Example 3 was about 530 nm in terms of the average arithmetic mean height Sa. Here, the same methods as in Example 1 were used to check these properties. Therefore, a description of these methods will be omitted. Comparative Example

[0061] [Comparative Example 1] In Comparative Example 1, the selectivity of plating, the smoothness of the plating film surface, and the adhesion of the plating film to the resin material were confirmed in the same manner as in Example 1. In Comparative Example 1, the same resin material as in Example 1 was prepared as a test specimen. In Comparative Example 1, the steps shown in the flow chart of FIG. 1 were carried out in the same manner as in Example 1 to form a conductor layer on the surface of the resin material.

[0062] In Comparative Example 1, the conditions that are different from those in Example 1 are that in the ultraviolet irradiation step, the difference in the arithmetic mean height Sa of the plated surface immediately before and immediately after the ultraviolet irradiation step is 1043 nm, in the alkaline degreasing step, the plated surface is immersed in a sodium hydroxide solution at 25° C. and the difference in the arithmetic mean height Sa of the plated surface immediately before and immediately after the degreasing step is 3 nm, in the sensitizing treatment step and the activating treatment step, the resin material is immersed for 45 seconds, and in the electroless nickel-phosphorus plating treatment step and the electroless copper plating treatment step, the temperature of the plating bath is 60° C. Details of each step shown in the flowchart in FIG. 1 have already been explained in Example 1, so they will not be repeated here.

[0063] Table 1 shows the results of checking the selective plating property, plating smoothness, and plating adhesion under the above-mentioned conditions. For reference, the surface roughness of the plating film in Comparative Example 1 was about 1600 nm in terms of the average arithmetic mean height Sa. Here, the same methods as in Example 1 were used to check these properties. Therefore, the explanation of these methods will be omitted.

[0064] [Comparative Example 2] In Comparative Example 2, the selectivity of plating, the smoothness of the plating film surface, and the adhesion of the plating film to the resin material were confirmed in the same manner as in Example 1. In Comparative Example 2, the same resin material as in Example 1 was prepared as a test specimen. In Comparative Example 2, a conductor layer was formed on the surface of the resin material by carrying out the steps shown in the flow chart of FIG. 1 in the same manner as in Example 1, except that the ultraviolet ray irradiation step was not carried out.

[0065] In Comparative Example 2, in addition to not performing an ultraviolet irradiation step, the conditions that differ from Example 1 are that in the alkaline degreasing step, the plated surface is immersed in a sodium hydroxide solution at 25° C., the difference in arithmetic mean height Sa of the plated surface immediately before and after the degreasing step is 1 nm, the resin material is immersed for 1 minute in the sensitizing treatment step and the activating treatment step, and the plating bath temperature is 60° C. in the electroless nickel-phosphorus plating treatment step and the electroless copper plating treatment step. Details of each step shown in the flowchart in FIG. 1 have already been explained in Example 1, so they will not be repeated here.

[0066] Table 1 shows the results of checking the selective plating property, plating smoothness, and plating adhesion under the above-mentioned conditions. For reference, the surface roughness of the plating film in Comparative Example 2 was about 620 nm in terms of the average arithmetic mean height Sa. Here, the same methods as in Example 1 were used to check these properties. Therefore, the explanation of these methods will be omitted.

[0067] [Comparative Example 3] In Comparative Example 3, the selectivity of plating, the smoothness of the plating film surface, and the adhesion of the plating film to the resin material were confirmed in the same manner as in Example 1. In Comparative Example 3, the same resin material as in Example 1 was prepared as a test specimen. In Comparative Example 3, the steps shown in the flow chart of Fig. 1 were performed in the same manner as in Example 1, except that the ultraviolet ray irradiation step and the alkaline degreasing step were not performed, and a conductor layer was formed on the surface of the resin material.

[0068] In Comparative Example 3, in addition to not performing the ultraviolet irradiation step and the alkaline degreasing step, the conditions that differ from Example 1 are that the resin material is immersed for 1 minute in the sensitizing treatment step and the activating treatment step, and that the plating bath temperature is 60° C. in the electroless nickel-phosphorus plating treatment step and the electroless copper plating treatment step. Details of each step shown in the flowchart in FIG. 1 have already been explained in Example 1, so they will not be repeated here.

[0069] Table 1 shows the results of checking the selective plating property, plating smoothness, and plating adhesion under the above-mentioned conditions. For reference, the surface roughness of the plating film in Comparative Example 3 was about 900 nm in terms of the average arithmetic mean height Sa. Here, the same methods as in Example 1 were used to check these properties. Therefore, the explanation of these methods will be omitted.

[0070] [Table 1]

[0071] (Results and Evaluation) From Table 1, the condition of the ultraviolet irradiation process of the present invention for the plated surface of the resin material is "the arithmetic mean height Sa of the resin material is 500 By satisfying the conditions of the present invention for the degreasing process, "irradiating the plated surface of the resin material with ultraviolet light to a degree that does not cause deformation of the surface, which is less than 1 nm in thickness," and "degreasing is performed by contacting the plated surface of the resin material with a degreaser at 25 to 60°C for 5 to 10 minutes," excellent results were obtained overall in terms of selective plating, plating smoothness, and plating adhesion. These results show that by satisfying these conditions, a conductor layer that realizes high-speed transmission of high-frequency signals can be formed on the surface of the resin material.

[0072] Furthermore, the specimens of Examples 1 and 2, which satisfied the condition of "10 nm to 1000 nm" for the difference in arithmetic mean height Sa of the plated surface immediately before and after the ultraviolet irradiation process and the condition of "3 nm to 10 nm" for the difference in arithmetic mean height Sa of the plated surface immediately before and after the degreasing process, showed superior results in selective plating and plating adhesion compared to other specimens that did not satisfy these conditions. From these results, it can be seen that by further satisfying these conditions, it is possible to obtain the effect of forming a conductor layer on the resin material surface that is fine but does not easily peel off or break. [Industrial Applicability]

[0073] According to the plating method of the present invention, it is possible to improve the adhesion between the resin material and the conductor layer and to stably form a conductor layer suitable for high-frequency circuits. Furthermore, it is possible to selectively form a conductor layer. Therefore, the plating method of the present invention can respond to the trend toward smaller, lighter, and higher performance electronic components, and also has the remarkable effect of being able to precisely form wiring (three-dimensional wiring) on ​​the surface of a resin material having a complex shape. In addition, since the plating method of the present invention does not require complex steps or equipment, it is advantageous in that it reduces the costs of equipment and processing and provides inexpensive products. Furthermore, the present invention is also suitable from an environmental perspective, since it does not require an etching process that roughens the surface of the resin material using hexavalent chromium, which is a harmful substance. [Explanation of symbols]

[0074] S10…UV irradiation process S20: Alkaline degreasing process S30…Sensitizing process S40: Activating process S50: Palladium removal process S60: Electroless nickel-phosphorus plating process S70: Electroless copper plating process

Claims

1. A plating method for forming a conductor layer only at portions of a resin material surface that are irradiated with ultraviolet light, comprising the steps of: an ultraviolet irradiation step of irradiating an ultraviolet ray to a plating target surface of the resin material having an arithmetic mean height Sa of 500 nm or less as measured in a non-contact manner using a laser microscope with an ultraviolet ray to an extent that does not cause deformation of the surface; a degreasing step in which, after the ultraviolet irradiation step, a degreasing agent at 25 to 60° C. is brought into contact with the plated surface of the resin material for 5 to 10 minutes to degrease the surface, The difference in the arithmetic mean height Sa of the plated surface immediately before and after the ultraviolet ray irradiation step is 10 nm to 60 nm; Then, a plating process is carried out to form the conductor layer.

2. 2. The plating method according to claim 1, wherein the difference in the arithmetic mean height Sa of the surface to be plated immediately before and after the degreasing step is set to 3 nm to 10 nm.

3. The plating process includes a sensitizing process in which the surface to be plated is brought into contact with a solution containing stannous chloride as a main component for 30 seconds to 3 minutes to adsorb tin ions; After the sensitizing treatment step, an activating treatment step is performed in which the surface to be plated is contacted with a solution containing palladium chloride as a main component for 30 seconds to 3 minutes to precipitate palladium; 3. The plating method according to claim 1, further comprising, after the activating treatment step, a conductor layer forming step of forming the conductor layer by plating on the surface to be plated.

4. The conductor layer forming step includes forming a nickel-phosphorus layer having a thickness of 0.1 to 5 μm on the surface to be plated, 4. The plating method according to claim 3, wherein a copper layer having a thickness of 10 to 35 μm is formed on the surface of the nickel-phosphorus layer.

5. 5. The plating method according to claim 3, wherein the temperature of the plating bath used in the conductor layer forming step is 50° C. to 80° C.

6. 6. The plating method according to claim 1, wherein the resin material is an epoxy resin material, a liquid crystal polymer material, a polyphenylene sulfide resin material, or an ABS resin material.

7. A wiring board obtained by using the plating method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Conductor track structure and method for manufacturing the same

    JP2004534408A

  • Metal-clad laminated sheet

    JP2008221489A

  • Sensitizing solution for electroless plating, and electroless plating method

    JP2010053435A

  • Aromatic polycarbonate composition

    JP2010536947A

  • Laminate and metal film formation method

    JP2017144632A